Husan Al-Tahallus (Proper Transition) in Al-Kumait’s Hashimites: A Study in Terms of Textual Linguistics - Muhammad Mahdi Hussein; Mustafa Sabah Mohda ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
This study aims at identifying Hashimites of Al-Kumait bin Zaid Al-Asadi and to know the effect of the term Husan Al-Tahallus (proper transition) in the text of the Hashimites. Thus, it explores this term from a textual point of view. Accordingly, the study is divided into introduction and two sections. The introduction deals with the definition of (proper transition) in language and its etymology. It traces the opinions of scholars of this term in the past and its connection with textual linguistics as well as the stages of structuring the poem at Al-Kumait. The first section analyzes the proper transition from the introduction to the themes on the text of the Hashimites. The second section revolves around the proper transition from the themes to the conclusion on the text of the Hashimites. It is known that the text of Hashimites is a collection of long poems recited by Al-Kumait bin Zaid Al-Asadi (60 AH - 126 AH) in which he called Muslims to support the Prophet’s Ahl al-Bayt (peace be upon him) (Al-Hashim) and the revolution against the Umayyad rule. As it is known, Al-Kumait was born during the days of murdering Al-Hussein (peace be upon him) in sixty. He is a well-known poet who was an expert in the languages of the Arabs at those days. Also, he was known for his Shiites to Bani Hashim. His Hashimite poems are the best evidence for this.